The Role of Local Wisdom in Shaping the Multicultural Character of Elementary School Students - Nizar Fikri, Ahmad; Istifadah; Dyah NawangSari (ATTA`DIB, 2025)
Abstract Multicultural education in elementary schools plays a strategic role in shaping students’ character from an early age, particularly through the integration of local wisdom. This study explores the role of local wisdom in shaping the multicultural character of students at MI Mamba’ul Ulum, Curahputih, Tegalwangi Village, Umbulsari District, Jember. This study employed a qualitative approach with a case study design. Data were collected through in-depth interviews with the principal, teachers, and students; observations of learning processes and extracurricular activities; and school documentation analysis. Data were analyzed using Miles & Huberman’s model, which includes data reduction, data display, and conclusion drawing. The findings revealed that local wisdom, such as values of mutual cooperation, tolerance, togetherness, and respect for differences, was effectively integrated into both classroom learning and non-formal activities. Students demonstrated positive development in appreciating diversity, both in classroom interactions and in their daily lives. These findings are consistent with recent studies emphasizing the importance of local wisdom–based education in strengthening multicultural attitudes. MI Mamba’ul Ulum has successfully utilized local cultural values as contextual educational media that are relevant to students’ needs and aligned with the demands of globalization. Keywords: local wisdom, multicultural education, elementary school, student character Abstrak Pendidikan multikultural di sekolah dasar memiliki peran strategis dalam membentuk karakter siswa sejak dini, terutama melalui integrasi kearifan lokal. Penelitian ini menyoroti peran kearifan lokal dalam membentuk karakter multikultural siswa di MI Mamba’ul Ulum, Curahputih, Desa Tegalwangi, Kecamatan Umbulsari, Jember. Penelitian ini menggunakan pendekatan kualitatif dengan desain studi kasus. Data dikumpulkan melalui wawancara mendalam dengan kepala sekolah, guru, dan siswa; observasi terhadap proses pembelajaran dan kegiatan ekstrakurikuler; serta analisis dokumentasi sekolah. Analisis data dilakukan dengan model Miles & Huberman, mencakup reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa kearifan lokal, seperti nilai gotong royong, toleransi, kebersamaan, serta penghormatan terhadap perbedaan, diintegrasikan secara efektif dalam proses pembelajaran maupun aktivitas non-formal. Siswa menunjukkan perkembangan positif dalam sikap menghargai keberagaman, baik dalam interaksi di kelas maupun dalam kehidupan sehari-hari. Temuan ini sejalan dengan penelitian terbaru yang menegaskan pentingnya pendidikan berbasis kearifan lokal dalam memperkuat sikap multikultural. MI Mamba’ul Ulum berhasil memanfaatkan potensi budaya lokal sebagai media pendidikan yang kontekstual, relevan dengan kebutuhan siswa, dan sesuai dengan tuntutan era globalisasi. Kata Kunci: kearifan lokal, pendidikan multikultural, sekolah dasar, karakter siswa.